(untitled) (Web of Teachers: Inderscience Research, 2024)
In our country, the creation of conditions for the comprehensive development and well-being of individuals, as well as ensuring their interests, has been a priority. As a result of systematic reforms aimed at raising the quality and efficiency of education to a new level, opportunities have been created for the wide application of interactive teaching methods to develop students’ creative abilities.